The efficacy of Makiang tea drinking on serum lipid profile in the treatment of dyslipidaemia: A randomized controlled trial - Wathita Phachonpai, Kitipong Wuthiyan, Anukul Junkaew, Kamin Suttikullabud, Rattaphong Pokkaew (Journal of Applied Pharmaceutical Science, 2024)
The purpose of this study was to investigate the effects of Makiang (MK) tea consumption on the serum lipid profile and oxidative stress biomarkers in participants with dyslipidemia. A randomized, single-blind, parallel-group, placebo-controlled study was conducted at the Outpatient Department of Phayao Hospital, Thailand. This clinical trial enrolled 64 subjects (males and females), aged between 30 and 65 years with hyperlipidemia who were randomized using simple random sampling, receiving a 12-week MK tea (3 g/250 ml hot water) taken daily or a placebo. Body mass index, lipid profile, and serum oxidative stress markers were evaluated at the baseline and the end of the study. Within-group comparisons revealed that drinking only one cup of MK tea daily caused a significant reduction (p < 0.05 all) of total cholesterol (TC), total triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C). Meanwhile, between-group differences showed that serum TC, TG, and LDL-C levels significantly decreased (p < 0.05 all), whereas the levels of high-density lipoprotein cholesterol were unchanged. This phenomenon was accompanied by decreased serum malondialdehyde and increased endogenous enzymatic defence systems (p < 0.05 all). Thus, MK tea may be useful as an adjunct agent to improve the lipid profile in patients with dyslipidemia.
Keywords: Cleistocalyx nervosum var. paniala, dyslipidemia, antioxidant, tea, Makiang